Host feeding preferences of sandflies in rural area, Southern Brazil - Muniz, Luís Henrique Garcia; Rossi, Robson Marcelo; Neitzke, Herintha Coeto; Monteiro, Wuelton Marcelo; Teodoro, Ueslei (Revista de Saúde Pública, 2006)
OBJECTIVE: To investigate the fauna and host feeding preferences of sandflies as for domestic animals in an endemic area of American cutaneous leishmaniasis. METHODS: The sandflies collections were carried out from 8:00 pm to 12:00 am in an area 40 meters away from one of the residences in a farm in Southern Brazil, between January and April, 2004. Collection was performed using four Falcão light traps, placed 5 m apart from each other beside a cage, each one of them containing an animal bait (swine, dog, rabbit, and chicken). RESULTS: A total of 1,697 specimens of sandflies were collected as follows: Nyssomyia whitmani, Pintomyia fischeri, Migonemyia migonei, Nyssomyia neivai, Pintomyia pessoai and Psathromyia shannoni. The prevalent species was N. whitmani. There were no feeding preferences of sandflies as for the animals studied. CONCLUSIONS: N. whitmani and P. fischeri are opportunistic species and female insects probably adjust their eating habits to host availability, suggesting eating eclecticism of these insects in anthropic environments.